PENGARUH PENGAWASAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI INSPEKTORAT KABUPATEN TASIKMALAYA - Setia Rachmanda, Yudi; Febiyani Lestari, Dheri (JURNAL EKONOMI PERJUANGAN, 2023)
The aims of this research are: 1). To find out about the supervisory measures implemented by the Tasikmalaya Regency Inspectorate. 2). To find out the motivation of Tasikmalaya Regency Inspectorate employees. 3). To find out the performance of Tasikmalaya Regency Inspectorate employees. 4). To determine the effect of supervision and motivation on the performance of Tasikmalaya Regency Inspectorate employees. The research method used is descriptive and verification methods. Data collection techniques were carried out through field research and literature study. The data analysis technique is carried out through Correlation Coefficient analysis to find the "r" value and Coefficient of Determination (KD) analysis to calculate the magnitude of the influence of supervision and motivation on employee performance. Meanwhile, to test the hypothesis, the "t" test is used.              The research results show that supervision, work motivation and employee performance at the Tasikmalaya Regency Inspectorate are in the very good category. The influence of supervision and work motivation on employee performance at the Tasikmalaya Regency Inspectorate is 67.40% and is supported by the calculated value (8.2592) > t table (2.015), so Ho is rejected and Ha is accepted. This means that supervision and work motivation have a significant influence on employee performance. Keywords: Supervision, Motivation, and Performance